ARE BEHAVIORAL BIASES INFLUENCED BY DEMOGRAPHIC CHARACTERISTICS & PERSONALITY TRAITS? EVIDENCE FROM PAKISTAN - Bashir, Taqadus; Azam, Nazish; Ali Butt, Arslan; Javed, Aaqiba; Tanvir, Ayesha (European Scientific Journal, ESJ, 2013)
The study investigates the influence of demographics (residential area, age, gender, marital status, education background) and personality traits (extraversion, openness, conscientiousness, neuroticism, and agreeableness) on the financial behavioral biases (overconfidence, herding/mass behavior and disposition effect) and risk taking behavior in Pakistan. The study will be beneficial for the financial advisors and individual investors. As it will help financial advisor to know potential behavioral biases in each type of investors while making investment decision and therefore they can advise investors properly to mitigate such biases. Personality dimensions are categorized under Big Five Personality model. Questionnaire survey method is used to collect the data from a Sample size of 225 respondents that includes bankers, finance students as well as investors. Structure equation modeling (SEM) analysis is used to analyze the impact of personality traits and demographics on the investment biases through Amos 20. The results show that big five personality traits have a significant relationship with overconfidence, herding/mass behavior and risk taking except disposition effect.